Academic Pressure and Health Habit Formation Among Scholars: Basis For Community Health Teaching - Bernal Jr., Hernando L.; Gumaru, Renz Chester R.; Go, Bernie B. (RIRAI Publisher, 2024)
This study aimed to evaluate the level of academic pressure experienced by university scholars in the Philippines across five dimensions: self-expectation, workload, despondency, study-related pressure, and worry about grades. Additionally, it examined the scholars' formation of health habits in six areas: water intake, rest, physical activity, nutrition/diet, temperance, and overall physical condition. The study also explored the relationship between academic pressure and health habits. Findings revealed that the scholars experienced a relatively high level of academic pressure, with self-expectation emerging as the most significant source. Conversely, the scholars exhibited a low level of healthy practices, particularly in the area of rest, which was identified as the least practiced health habit. On a positive note, temperance was highlighted as the most favorable health behavior, reflecting the scholars' ability to exercise moderation.